We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
43
1
avatar

\(\sum_{n=1}^{15} (2n-1)\)

 Apr 26, 2019
 #1
avatar+100549 
+2

First term  = 2(1) - 1  = 1

15th term  = 2(15) - 1  = 29

 

Sum  =  [ first term +last term ] * number of terms  / 2  = 

 

 [ 1 + 29 ] * 15 / 2  =

 

[30] * 15  / 2   =

 

450  / 2  =

 

225

 

 

cool cool cool

 Apr 26, 2019

20 Online Users

avatar
avatar
avatar
avatar